Effect of Holding Time During Sintering on Microstructure and Properties of 3D Printed Alumina Ceramics - Pan, Yu; Li, He; Liu, Yongsheng; Liu, Yansong; Hu, Kehui; Wang, Ning; Lu, Zhigang; Liang, Jingjing; He, Sujun (Frontiers in Materials, 2020)
In this work, alumina ceramics were formed via stereolithography based 3D printing technology. Effects of holding time during sintering on microstructure and properties of alumina ceramics were investigated. Sintered alumina ceramics were made up of layered structures due to layer-by-layer forming method. In addition, interlayer spacing decreased with the increase in holding time. Average particle size, shrinkage, crystallite size, flexural strength, and hardness increased with the increase in holding time due to strong interfacial bonding among alumina particles. Open porosity decreased slightly as holding time increased. Moreover, it was found that holding time had little influence on bulk density, phase composition, and chemical bonds of the ceramic. The shrinkage in Z direction was about 1.8 times higher than that in X or Y direction due to layered structure caused by 3D printing forming method. The optimum holding time was 90 minutes, which resulted in ceramic product with interlayering spacing of 11.8 μm, shrinkage of 2.1% in X direction, 2.1% in Y direction, and 4.1% in Z direction, flexural strength of 20.7 MPa, hardness of 17.6 GPa, Vickers hardness of 114.3 HV, bulk density of 2.5 g/cm3, and open porosity of 39.0%.